The Risk Assessment of Occupational Safety Using Job Safety analysis ( JSA) at PT. P&P Lembah Karet Padang - Rahman, A; Djafri, D; Triana, V (KnE Life Sciences, 2019)
Occupational accident has been a big problem for most of industry in the developing countries. This research aimed to know the condition of occupational risk level at PT. P&P Lembah Karet Padang. This research was conducted in the sections that have large number of occupational accident and repeatedly occured. The primary data were obtained from observations, while secondary data were obtained from the archive of the factory. The analysis method was Job Safety analysis ( JSA) which consisted of hazard identification, risk assessment and risk control recommendation. The result of this research was presented in figures and tables which described that there were still high risk in Timbang Section, Gilingan Section and Press section, shown by red color code. There were still some medium and low risk too, shown by yellow and green color code. Based on the result, it can be concluded that there were still high risk and medium risk in some sections of PT. P&P Lembah Karet Padang, that could not been controlled yet, which caused occupational accident that occurred time aftertime. It is suggested to the factory to apply the recommended risk contol in order to decrease or remove the same occupational accidents that may happens in the future. Keywords: Job Safety Analysis ( JSA), Occupational Safety, Occupational Accident, Risk Assessment